Evaluation of Health Hazard and Governance Performance of Air Pollution: A Case Study of Z City - Cui, Ying; Shi, Yunxia (Frontiers in Public Health, 2022)
Based on the date of the main pollutant discharge and change of pollutant concentration in Z city, this paper performed the statistical analysis of the concentration data in excel. The data covers three years from January 1st, 2015 to December 31st, 2017. An exposure-response relationship model was used established to evaluate the health hazards caused by air pollution and the corresponding economic losses, further analyzed the relationship among air pollution, health hazards and economic benefits. The results of the study showed that the changes of SO2 and NO2 concentrations in Z City from 2015 to 2017 have great influence on the mortality rate of local population, respiratory mortality, the rate of internal medicine of outpatients and the rate of chronic bronchitis disease. The economic losses between 2015 and 2017 caused by PM10, the primary pollutant in the air, were 3.9 billion, 3.5 billion and 2.9 billion respectively, accounting for 3.60%, 2.88% and 2.09% of Z City’s GDP were enormous. Finally, countermeasures of feasible treatment, and countermeasures in government performance were put forward.